On a class of closed cocycles for algebras of non-formal, possibly unbounded, pseudodifferential operators - Magnot, J.-P. (Methods of Functional Analysis and Topology, 2022)
In this article, we consider algebras A of non-formal pseudodifferential operators over S^1 which contain C^∞(S^1), understood as multiplication operators. We apply a construction of Chern-Weil type forms in order to get 2k-closed cocycles. For k=1, we obtain a cocycle on the algebra of (maybe non classical) pseudodifferential operators with the same cohomology class as the Schwinger cocycle on the algebra of classical pseudodifferential operators, previously extended and studied by the author on algebras of the same type. У цій статті ми розглядаємо алгебри A неформальних псевдодиференціальних операторів над S^1, які містять C ^ ∞ (S ^ 1) і розглядаються як оператори множення. Застосовується конструкцію форм типу Черна-Вейля, для отримання 2k-замкнених коциклів. Для k = 1 , ми отримуємо коцикл на алгебрі псевдодиференційних операторів (можливо, некласичній) з тим самим класом когомологій, що і коцикл Швінгера на алгебрі класичних псевдодиференціальних операторів, який був раніше розширений і вивчений автором на алгебрах того ж самого типу.